Modeling and measurement of temperature and draw solution concentration induced water flux increment efficiencies in the forward osmosis membrane process - Wang, Qun; Zhou, Zongyao; Li, Jinqiang; Tang, Qingchen; Hu, Yunxia (Desalination, 2019)
Water/energy sustainability has initiated strong academic interests in the development of forward osmosis (FO) to produce clean water. High water flux is critical to operate FO efficiently in industrial applications. Operation parameters including draw solution (DS) concentration and temperature highly affect water flux. As such, we investigated impacts of DS concentration and temperature on water fluxes of one commercial thin-film composite FO membrane via theoretical analysis and experimental measurement. Solution-diffusion model was revised by incorporating all concentration/temperature-related parameters. Results demonstrated the validity of revised SD model by comparing experimental and theoretical water fluxes at a wide DS concentration/temperature range. Concentration/temperature-induced water flux increment efficiencies (CIE and TIE) were introduced to quantify utilization efficiencies of high-salinity water and heat. Results revealed that water fluxes were increased with the increase of both DS concentration (0.5–5.0 M) and temperature (18–50 °C). However, the CIE decreased with the increase of DS concentration, but increased with the increase of temperature. Furthermore, the TIE increased with the increase of both DS concentration and temperature from 25 to 47 °C. Correlation coefficient of CIE and TIE was defined and calculated to optimize the FO process efficiency through identifying favorable zones of DS concentration and temperature. [Display omitted] •SD model was revised by incorporating temperature/concentration-related parameters.•Revised model was suitable at different concentrations and temperatures.•Two indexes can quantity utilization efficiencies of salinity and temperature.•Concentration/temperature-sensitive zone was determined by proposed protocol.